Three new acenaphthene derivatives from rhizomes of Musa basjoo and their cytotoxic activity. Issue 8 (3rd April 2021) - Jiang, Li; Zhang, Bao; Wang, Yang; Sun, Jia; Ma, Xue; Wang, Guangcheng; Fu, Sihong; Lin, Changhu; Li, YongJun
Abstract: Three new acenaphthene derivatives cis -3-(4'-methoxyphenyl)-acenaphthene-1, 2-diol (1 ), trans -(1 S, 2 S )-3-phenyl-acenaphthene-1, 2-diol (2 ) and 8-(4-hydroxyphenyl)-2H-acenaphthylen-1-one (3 ) in company with six known compounds were isolated from the 70% ethanol extract of the rhizomes of Musa basjoo . Those chemical constituents were separated and purified by macroreticular resin, silica gel, Toyopearl HW-40F, SephadexLH-20 and other chromatographic methods, respectively. The chemical structures of new compounds were elucidated by HR-ESI-MS, 1 H NMR, 13 C NMR, HMQC, HMBC spectrum and specific optical rotations. Compound 4 was isolated for the first time from the genus Musa and compound 7 was firstly assigned the carbon spectrum. Furthermore, the cytotoxic activity of compounds 1–9 against WM9, MDA-MB231, HeLa, K562, DU145 and PC3 was screened with cisplatin as a positive control. Compound 9 showed promising cytotoxic activities with IC50 values of 2.65 ± 0.38 µM against the HeLa cell lines, while compound 8 possessed significant cytotoxicity with IC50 values of 6.51 ± 0.44, 18.54 ± 0.68 and 7.98 ± 1.44 µM against the HeLa, MDA-MB231 and WM9 cell lines, respectively. Graphical Abstract: